Detrminants of financial performance of two top banks in five (5) Asian countries / Muhammad Haziq Fitri Mohd Fuzi - Mohd Fuzi, Muhammad Haziq Fitri (2022)
Banking sector has grown to be the most prominent and important industry in Malaysia and every country across the globe (Pratiwi, 2012). This is because the banking industry is necessary for the economy to be function. In economic system, the banking industry plays a critical role in the development and implementation of financial policies. Hence, the stability and growth of economic for every country is depending on the strength of the banking system (Halling & Hayden, 2006). A banking system can be well-defined as a group of financial institutions that offer the financial services to the community (Aithal, 2016). The example of financial institutions are commercial banks, investment banks, retail banks, cooperative banks, and others.